Creative architectural design with children: a collaborative design project informed by Rhodes's theory. Issue 3 (1st October 2016) - Xu, Leilei; Izadpanahi, Parisa
Abstract : Since the United Nations adopted the Convention on the Rights of the Child in 1989, there has been global consensus that children need to be involved in the planning and design of their environment. There exist various international initiatives that support collaborative design with children, with co-design projects conducted in different areas of the world. Evolving from the global context of co-design, this project explores creativity in relation to architectural design with children. Between October and December 2011, a team of architecture students from Deakin University worked with children from Roslyn Primary School (both institutions located in Victoria, Australia) to design a playground structure. Informed by Rhodes's (1961) theory, creativity in this co-design project was addressed through the four dimensions of creative designers, creative context, creative process, and creative design outcomes. The findings of this study corroborate Rhodes's theory of creativity, and suggest that it is useful to engender creative architectural design with children.